2022
DOI: 10.1111/emip.12484
|View full text |Cite
|
Sign up to set email alerts
|

Mode Effects in College Admissions Testing and Differential Speededness as a Possible Explanation

Abstract: As testing programs transition from paper to online testing, they must study mode comparability to support the exchangeability of scores from different testing modes. To that end, a series of three mode comparability studies was conducted during the 2019–2020 academic year with examinees randomly assigned to take the ACT college admissions exam on paper or online. Unlike many prior mode comparability studies, examinees testing online earned higher scores on average than examinees testing on paper, especially o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Others proposed differences in test-taking behavior as a potential explanation. For example, test-takers tend to take less time on the computer and finish tests quicker, while showing higher guessing behavior, particularly among low-performance students ( Karay et al, 2015 ; Singer et al, 2019 ); albeit also opposite results were sometimes observed ( Steedle et al, 2022 ). An experimental study that independently varied the presentation medium (paper versus computer) of the reading text and the test items suggested that the mode effect in reading comprehension is primarily a result of digital reading rather than a media-induced testing effect ( Ben-Yehudah & Eshet-Alkalai, 2021 ).…”
Section: Characteristics Of Remote Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Others proposed differences in test-taking behavior as a potential explanation. For example, test-takers tend to take less time on the computer and finish tests quicker, while showing higher guessing behavior, particularly among low-performance students ( Karay et al, 2015 ; Singer et al, 2019 ); albeit also opposite results were sometimes observed ( Steedle et al, 2022 ). An experimental study that independently varied the presentation medium (paper versus computer) of the reading text and the test items suggested that the mode effect in reading comprehension is primarily a result of digital reading rather than a media-induced testing effect ( Ben-Yehudah & Eshet-Alkalai, 2021 ).…”
Section: Characteristics Of Remote Testingmentioning
confidence: 99%
“…Particularly, for cognitive measurements in educational contexts computerized proficiency testing has become the de facto standard in many applied areas. For example, many high-stake college admission or proficiency certification procedures adopt computerized testing formats (e.g., Hurtz & Weiner, 2022;Steedle et al, 2022) because they allow for better standardization of test instructions, item presentations, and response coding, thus, leading to less error-prone and fairer measurements. Even many educational large-scale studies have recently switched to computers as their preferred medium of assessment that also allows for administering innovative item formats (e.g., simulation-based items) and collecting ancillary information (e.g., process data) to capture novel constructs more precisely (see von Davier et al, 2019).In recent years, psychological assessments have faced another significant shift.…”
mentioning
confidence: 99%